Professional Vision of Pre-service Biology Teachers Focused on Subject and Subject Didactics Phenomena - Pavlasová, Lenka (Scientia in educatione, 2017)
Professional vision represents one dimension of teachers’ professionalism. The general consensus is that it should be developed during the standard teacher-training process. In order to choose an effective intervention mechanism, the teacher needs to be familiar with the proficiency of the students at the beginning of the teaching process. The submitted study focuses on pre-service biology teachers (n = 26), with the aim of assessing their noticing abilities and knowledge-based reasoning skills. These are detected by a qualitative analysis of written reflections on videos of someone else’s teaching. Using the category system devised by Sherin and van Es (2009) it was found that students’ reflections contained more statements focused on the teacher and pedagogy, typically expressing a descriptive and evaluative stance. Further analysis showed that statements associated with the pupils were more often interpreted by students than the ones associated with the teacher, where description and evaluation tended to be the predominant stances. Statements associated with subject and subject didactics can be thematically divided into two broad groups: (1) methods, forms, process and concept of teaching and (2) goal of teaching, expected outcomes, competencies, content of teaching. Neglected topics are e.g. teaching aids, motivation, activation and attention of pupils, teacher’s instructions and teacher’s mistakes. The presented findings provide important information for the guarantors of courses specializing in the didactics of biology.